Analysis of the Relationship Between Local Climate Zone and Land Surface Temperature in Padang City - Agung Pratama; Fajrin Fajrin; Defwaldi Defwaldi (Pusat Riset dan Inovasi Nasional, 2025)
Changes in the earth's surface temperature can have significant impacts on climate, environment, human health, and ecological systems. Global warming becomes increasingly complex when applied to urban contexts, which often experience urban heat island (UHI) effects. This study aims to analyze the relationship between Local Climate Zone (LCZ) and Land Surface Temperature (LST) in Padang City. This study identifies the distribution pattern of LCZ and relates it to surface temperature variability. The data used to map the local climate zone using samples made using WUDADPT and to determine land surface temperature using Landsat 8 OLI/TIRS C1 Level 1 Satellite Imagery. The results of this study are that the Local Climate Zone (LCZ) in Padang City consists of 13 classifications. The type of building that dominates Padang City is Open Low-rise. Meanwhile, Densee Trees dominate the type of natural land cover in Padang City. Land Surface Temperature (LST) in Padang City is dominated by low temperatures covering an area of ​​43,987.94 Ha. The relationship between LCZ and LST in Padang City has a coefficient of determination of 0.608, which means that the level of relationship between LCZ and LST shows a moderate relationship with the greatest influence occurring in the heavy industry classification with a coefficient of determination of 0.904, which means that the influence of heavy industry on temperature is 90.4% or very strong.